Identifying characteristics and typology of small shrinking towns in Serbia: The case of the Region of Southern and Eastern Serbia - Ljubenović, Milica; Bogdanović Protić, Ivana; Dinić Branković, Milena; Đekić, Jelena; Igić, Milica (Acta geographica Slovenica, 2015)
Small towns are highly exposed to urban shrinkage, but the attention to them has still been weak in the research, especially in Serbia. Therefore, this study deals with small towns in the Region of Southern and Eastern Serbia, with the goal of elaborating a typology of small towns based on shrinking characteristics. Shrinking small towns were first mapped and then grouped using principal component and cluster analysis. The results indicate that the patterns of shrinking differ and that four clusters of shrinking towns with distinguishable specific characteristics can be identified. This research contributes to understanding of different causes and trajectories of small shrinking towns and suggests a possible application of presented methodology as an urban planning tool.